Respuestas
Respuesta dada por:
0
Tu ecuación sería asi:
![8 {m}^{2} + 14m - 9 = 0 8 {m}^{2} + 14m - 9 = 0](https://tex.z-dn.net/?f=8+%7Bm%7D%5E%7B2%7D++%2B+14m+-+9+%3D+0)
por aspa seria:
![(4m + 9)(2m - 1) = 0 (4m + 9)(2m - 1) = 0](https://tex.z-dn.net/?f=%284m+%2B+9%29%282m+-+1%29+%3D+0)
esto te daría dos respuestas:
la primera seria:
![4m + 9 = 0 \\ 4m = - 9 \\ m = \frac{ - 9}{4} 4m + 9 = 0 \\ 4m = - 9 \\ m = \frac{ - 9}{4}](https://tex.z-dn.net/?f=4m+%2B+9+%3D+0+%5C%5C+4m+%3D++-+9+%5C%5C+m+%3D++%5Cfrac%7B+-+9%7D%7B4%7D+)
la segunda seria:
![2m - 1 = 0 \\ 2m = 1 \\ m = \frac{1}{2} 2m - 1 = 0 \\ 2m = 1 \\ m = \frac{1}{2}](https://tex.z-dn.net/?f=2m+-+1+%3D+0+%5C%5C+2m+%3D+1+%5C%5C+m+%3D++%5Cfrac%7B1%7D%7B2%7D+)
por aspa seria:
esto te daría dos respuestas:
la primera seria:
la segunda seria:
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años